ANALISIS PENGARUH PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI (Studi kasus Pada Pua-pua Cafe Timika) - Salmia Salmia; Maria Fransiska Penaten Raya (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of product, price, and service quality on purchasing decisions through purchase intention. The method used in this research is the associative method. The data collection techniques used by researchers are observation techniques and questionnaires. The analysis technique used in the research is quantitative analysis technique using multiple linear regression analysis. Overall, the results of this study confirm that the influence of product, price, and service quality does not have a significant role in influencing purchasing decisions either directly or through purchase intention at Pua-pua Cafe.